Line defects and temperature effects in liquid crystal tunable planar Bragg gratings - Snow, B.D.; Adikan, Faisal Rafiq Mahamd; Gates, J.C.; Gawith, C.B.E.; Dyadyusha, A.; Kaczmarek, M.; Smith, P.G.R. (2007)
Liquid crystal tunable planar Bragg Gratings produced by Direct UV Writing are capable of wavelength tuning of over 100GHz. However, such devices exhibit non-linear tuning curves with threshold points and hysteresis. We show that these effects are due to the formation of disclination structures in the liquid crystal and discuss the role of electrode defects and sample temperature on wavelength tuning. (C) 2007 Optical Society of America.